What we've become - Nelson, Jennifer (Filmmaker); Dresser, Diana; Arnette, Crystal; Nuccio, Michael; Through a Glass Productions; Leomark Studios ([Lawrence, Kansas] : Through a Glass Productions, 2016)
When her mother suffers a heart attack, successful New York writer Stephanie Golden sets aside her job and fiancé to return to her hometown in Kansas. There she finds a family in turmoil and her younger sister Monica sinking into the dark world of drug addiction. As Monica spirals out of control, Stephanie seeks the help of former classmate and recovering addict Billy. Stephanie struggles to confront Monica about her addiction while dealing with her unexpected feelings for her old friend. Though her hometown is haunted with painful memories, Stephanie must find the courage to save her sister no matter the cost. --
Originally released as a motion picture in 2017.
Diana Dresser, Crystal Arnette, Michael Nuccio, Janice Craft, Brian Paulette, Anika Paulette, Christopher Hayes with Mark Devine and Keith Loneker Sr.
Cinematographer, Jeremy Osbern ; editor, Stephen Deaver ; music, Wes Urbaniak.
In English; closed captioning available.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 30, 2020)
Keywords: Dysfunctional families -- Fiction; Mothers and daughters -- Fiction; Sisters -- Fiction; Drug addiction -- Fiction; Homecoming -- Fiction; Kansas -- Fiction; Fiction films; Feature films; Internet videos; Streaming video